Computer aided design modelling and finite element analysis of premolar proximal cavities restored with resin composites - Matuda, Amanda Guedes Nogueira [UNESP]; Silveira, Marcos Paulo Motta [UNESP]; De Andrade, Guilherme Schmitt [UNESP]; Piva, Amanda Maria De Oliveira Dal [UNESP]; Tribst, João Paulo Mendes; Borges, Alexandre Luiz Souto [UNESP]; Testarelli, Luca; Mosca, Gabriella; Ausiello, Pietro (MDPI, 2021)
This study evaluated the stress distribution in five different class II cavities of premolar models restored with conventional or bulk-fill flowable composite by means of finite element analysis (FEA) under shrinkage and occlusal loading. An upper validated premolar model was imported in the software, and five class II cavities with different occlusal extensions and dimensions were prepared: horizontal cavity on the mesial surface (horizontal slot), mesio-occlusal cavity, mesial cavity (vertical slot), tunnel type cavity and direct access cavity. The models were restored with conventional or bulk-fill flowable resin composite. The tested materials were considered as homogeneous, linear, and isotropic. The Maximum Principal Stress criteria was chosen to evaluate the tensile stress results. The lowest shrinkage stress value was observed in the direct access cavity restored with bulk-fill flowable resin composite (36.12 MPa). The same cavity, restored with conventional composite showed a score of 36.14 MPa. The horizontal slot cavity with bulk-fill flowable showed a score of 46.71 MPa. The mesio-occlusal cavity with bulk-fill flowable had a score of 53.10 MPa, while with conventional composite this was 55.35 MPa. Higher shrinkage stress was found in the vertical slot cavity with conventional resin 56.14 MPa, followed by the same cavity with bulk-fill flowable 56.08 MPa. Results indicated that the use of bulk-fill flowable composite resin more significantly decreased the polymerization shrinkage stress magnitude. The larger the cavity and the volume of material necessary to restore the tooth, the greater the residual stress on enamel and dentin tissue.
Keywords: Dental inlays; Dental materials; Dental prosthesis; Finite element analysis; Mechanical stress